2021
DOI: 10.1093/heapol/czab075
|View full text |Cite
|
Sign up to set email alerts
|

Modified scoping review of the enablers and barriers to implementing primary health care in the COVID-19 context

Abstract: Since the Alma Ata Declaration of 1978, countries have varied in their progress towards establishing and sustaining comprehensive primary health care (PHC) and realizing its associated vision of ‘Health for All’. International health emergencies such as the coronavirus-19 (COVID-19) pandemic underscore the importance of PHC in underpinning health equity, including via access to routine essential services and emergency responsiveness. This review synthesizes the current state of knowledge about PHC impacts, imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 92 publications
(185 reference statements)
1
16
0
Order By: Relevance
“…Therefore, the effective containment of COVID-19 and future epidemics must include determined efforts to restructure African health systems and make them more effective, adaptative, and resilient. This restructuration will also help avoid the interruption of essential services (37,39).…”
Section: Implications For Primary Health Carementioning
confidence: 99%
“…Therefore, the effective containment of COVID-19 and future epidemics must include determined efforts to restructure African health systems and make them more effective, adaptative, and resilient. This restructuration will also help avoid the interruption of essential services (37,39).…”
Section: Implications For Primary Health Carementioning
confidence: 99%
“…But while universal health coverage (UHC) is one of the main development goals adopted by the United Nations and the World Health Organization (WHO), the COVID-19 crisis has clearly shown that achieving UHC at a sufficiently optimal level and protection of the most vulnerable population groups remains an unresolved problem even for the richest countries. Therefore, many health professionals and WHO experts propose number of measures to increase the resilience of health systems to ensure universal health coverage and health security during the COVID-19 pandemic and beyond [29,30].…”
Section: Un Political Declaration On Universal Healthmentioning
confidence: 99%
“…The PHC approach incorporates multisectoral policy and actions and emphasises human dignity and rights [ 12 ]. Community-based PHC systems could provide comprehensive, affordable, and acceptable health services at the first point of contact in the PHE contexts [ 13 , 14 ]. Responses to PHEs can be ensured by developing interdisciplinary teams, designing comprehensive interventions, and working with civil societies and communities [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%